(untitled) (Research, Society and Development, 2023)
This article theoretically analyzes the concepts of school and fair school, seeking a reflection on their strengths and difficulties. This is an exploratory research with a qualitative approach. To develop it, the narrative review technique was used, which allows the construction of articles in which the authors can carry out broader critical analyzes and interpretations. Revealing that a school can only be fair when it overcomes the belief in an ideal of school justice, but when it combines different principles of justice, a process that distances itself from judgments and simplistic assumptions, which seek miraculous solutions. It is suggested that future studies address justice and education, mobilizing analyzes on advances in the right to education, the limits and potential of educational policies and the dynamics experienced in the micro school field, and how such policies have repercussions in terms of school practices and principles of justice that emerge on the school floor.